(untitled) (Journal of International Studies, 2024)
This article described and analyzed the dilemma faced by ASEAN under its non-interference principle in managing the human rights issues in Myanmar. The presence of that principle severely curtails ASEAN’s firm action to promote and protect human rights strongly based on the ASEAN’s commitment written in the ASEAN Charter and the ASEAN Declaration of Human Rights (ADHR). This article utilizes the qualitative research method supported by secondary data to provide an in-depth and comprehensive analysis. ASEAN’s protection of human rights is reflected by its active conduct of regular discussions and engagements on human rights issues in the region, the adoption of the ADHR, and the establishment of the ASEAN Intergovernmental Commission on Human Rights (AICHR). The human rights issues gained more attention in ASEAN in 1997 as the United States and European Union opposed the ASEAN decision to accept Myanmar as a member on the grounds of the human rights violations record in Myanmar. The membership in ASEAN did not improve the human rights record in Myanmar as ASEAN had hoped for. Myanmar embarked on other human rights violations, among others the Rohingya crisis (2012) and the military coup against the democratic government (2021) that sparked criticism from abroad and within ASEAN. This study concluded that the principle of noninterference has set the limit and curtailed ASEAN’s contribution toward optimally addressing human rights violations in Myanmar. ASEAN may need in the future a new and comprehensive mechanism for addressing human rights violations. A stronger constructive engagement policy should be put in place to set a universal standard to protect human rights in the region.